HEALTH BELIEF MODEL PADA IBU HAMIL DALAM PERILAKU MENGHITUNG GERAK JANIN - Yessika Riski Melati; Nur Eva Aristina; Ika Yudianti (Jurnal Ilmiah Kebidanan Imelda, 2024)
Monitoring the well-being of the fetus is an important part of the management of pregnancy and childbirth. Health Belief Model (HBM) is a model of individual health beliefs in determining attitudes to do or not to do health behavior. The purpose of this study was to describe the description of the Health Belief Model in pregnant women in the behavior of counting fetal movements during pregnancy. This type of research is descriptive quantitative with a total sample of 30 pregnant women who have felt fetal movement. The sampling technique uses accidental sampling. The research was conducted in July 2022 at PMB Santi Rahayu, Malang Regency. The research instrument used the Health Belief Model questionnaire. The results showed that the most negative perceptions were in the perceived barriers variable (60%) and positive perceptions in the cues to action variable (60%). From the result of the researh it is hoped that midwives can teach how to calculate fetal movement so that pregnant women can apply it independently.